Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1963
DOI: 10.1055/s-0038-1654795
|View full text |Cite
|
Sign up to set email alerts
|

Zusammenhänge zwischen Konstitution und Wirkung bei Hemmstoffen der Fibrinolyse

Abstract: ZusammenfassungDie antifibrinolytische Aktivität der e-Aminocapronsäure ist an ihre freie Aminound Carboxylgruppe und an den Abstand dieser beiden Gruppen voneinander gebunden. Substitutionen an beiden Gruppen oder Veränderungen ihres Abstandes führen zu einer Verminderung der antifibrinolytischen Aktivität. Zyklische Verbindungen sind ebenfalls antifibrinolytisch aktiv, wenn sie eine terminale Aminound Carboxylgruppe in einem entsprechenden Abstand voneinander besitzen. Derartige Verbindungen sind die p-Amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

1965
1965
1978
1978

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…This problem of therapeutic interference with fibrinolysis was solved satisfactorily with the development of synthetic antifibrinolytics -such as e-aminocaproic acid (EACA), aminomethylcyclohexane carboxylic acid (AMCA) andp-aminomethylbenzoic acid (PAMBA) (4,11,16).…”
Section: Inhibitors O F Fibrinolysismentioning
confidence: 99%
“…This problem of therapeutic interference with fibrinolysis was solved satisfactorily with the development of synthetic antifibrinolytics -such as e-aminocaproic acid (EACA), aminomethylcyclohexane carboxylic acid (AMCA) andp-aminomethylbenzoic acid (PAMBA) (4,11,16).…”
Section: Inhibitors O F Fibrinolysismentioning
confidence: 99%
“…Die Antifibrinolytika EACA, P AMBA und AMCA sind chemisch ahnlich strukturierte Verbindungen. Sie besitzen je eine endstandige Karboxyl-und Aminogruppe, die in einem Abstand von ungefahr 7 A voneinander angeordnet sind (2,5). Der Mechanismus, durch welchen die Hemmung des Fibrinolysevorganges zustandekommt, ist deshalb bei diesen Verbindungen der gleiche.…”
Section: Besprechungunclassified
“…The action of the synthetic antifibrinolytics s-aminocaproic acid (EACA) (Okamoto 1959;Okamoto et al 1959), p-aminomethylbenzoic acid (PAlVIBA) (Lohmann et al 1963(Lohmann et al , 1964, and trans-4-aminomethylcyclohexane carboxylic acid (trans-AMCHA) (Melander et al 1964;Okamoto et al 1964) is generally thought to be caused by an inhibition of the activation of the fibrinolytic enzyme, plasmin, from its inactive precursor plasminogen. This "antiactivator activity" of the antifibrinolytics was first described by Alkjaersig et al (1959) and repeatedly confirmed later (for review see Markwardt and Landmann 1967).…”
Section: Introductionmentioning
confidence: 99%